2005
DOI: 10.1074/jbc.m411855200
|View full text |Cite
|
Sign up to set email alerts
|

Endoproteolytic Cleavage of FE65 Converts the Adaptor Protein to a Potent Suppressor of the sAPPα Pathway in Primates

Abstract: Adaptor protein FE65 (APBB1) specifically binds to the intracellular tail of the type I transmembrane protein, ␤-amyloid precursor protein (APP). The formation of this complex may be important for modulation of the processing and function of APP. APP is proteolytically cleaved at multiple sites. The cleavages and their regulation are of central importance in the pathogenesis of dementias of the Alzheimer type. In cell cultures and perhaps in vivo, secretion of the ␣-cleaved APP ectodomain (sAPP␣) is the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 53 publications
4
33
0
Order By: Relevance
“…7B, bottom blot). The size of the observed protein matches the p65Fe65 endoproteolytic protein product reported previously (18). Interestingly, this proteolytic cleavage maps to the amino-terminal portion of Fe65.…”
Section: Fe65 Stimulation Of App Proteolysis Is Dependent On Ptb1-supporting
confidence: 59%
See 3 more Smart Citations
“…7B, bottom blot). The size of the observed protein matches the p65Fe65 endoproteolytic protein product reported previously (18). Interestingly, this proteolytic cleavage maps to the amino-terminal portion of Fe65.…”
Section: Fe65 Stimulation Of App Proteolysis Is Dependent On Ptb1-supporting
confidence: 59%
“…Various studies have concluded that Fe65 either inhibits or promotes secretion of APP s␣ (10,12,18). The results of our analysis of AICD production indicate that Fe65 promotes cleavage of APP by ␣-secretase, a conclusion that implies that Fe65 should increase rather than decrease production of APP s␣ .…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Around 20 proteins have been demonstrated to interact with AICD, one of them being Fe65 (Bórquez and González-Billault, 2012). Fe65 is able to bind AβPP and it acts as a potent modulator controlling the balance between the non-amyloidogenic and amyloidogenic pathways (Hu et al, 2005). AICD also functions as a transcription factor and regulates a number of cellular processes, one being a negative feedback loop, decreasing AβPP trafficking to the cell surface by binding to the promotor site for Wiskott-Aldrich syndrome protein (WASP)-family verprolin homologous protein 1, WAVE1 (Ceglia et al, 2015).…”
Section: Physiological Function Of Aβpp and Its Cleavage Productsmentioning
confidence: 99%